2020
DOI: 10.1155/2020/3647525
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Prescriptions Decrease Diarrhea Rate by Relieving Colonic Inflammation and Ameliorating Caecum Microbiota in Piglets

Abstract: Diarrhea is a leading cause of death in piglets. XiaoJianZhong (XJZ) and Jingsananli-sepsis (JSS) were two traditional Chinese medicine (TCM) prescriptions to prevent and treat intestinal diseases, including diarrhea and inflammatory disease. Here, we investigated the effects of XJZ and JSS on diarrhea rate, growth performance, colonic inflammation, and caecum microbiota in piglets. A total of 18 piglets were selected and randomly divided into three groups. Control group was supplied with basal diets, while TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Experimental groups included: (I) Control group (basal diet), (II) XJZ group (basal diet plus 10 g/kg XJZ prescription), or (III) JSS group (basal diet plus 3 g/kg JSS prescription). The doses for TCM groups (XJZ and JSS) were determined based on our preliminary tests and previous study (9). All raw materials for XJZ and JSS prescriptions were provided by The Spirit Jinyu Biological Pharmaceutical Co., Ltd (Huhhot, Inner Mongolia, China).…”
Section: Animals Experimental Design and Rationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental groups included: (I) Control group (basal diet), (II) XJZ group (basal diet plus 10 g/kg XJZ prescription), or (III) JSS group (basal diet plus 3 g/kg JSS prescription). The doses for TCM groups (XJZ and JSS) were determined based on our preliminary tests and previous study (9). All raw materials for XJZ and JSS prescriptions were provided by The Spirit Jinyu Biological Pharmaceutical Co., Ltd (Huhhot, Inner Mongolia, China).…”
Section: Animals Experimental Design and Rationsmentioning
confidence: 99%
“…However, the mechanism is still not fully understood. Previous study showed that both XJZ and JSS could increase the growth performance and control diarrhea induced by weaning in piglets (9,12,13).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Butyrivibrio could ferment glucose to produce butyrate, which was beneficial for supplying energy for the gut cell and the growth of beneficial bacteria (31,72). The reason for the current findings might be that Chinese medicine could help decrease colonic or caecal pH levels, enhance the abundance of the beneficial microbial community, and colonic inflammation response via downregulating the TLR4/MyD88/NF-κB signaling pathway and reducing mRNA expression of some pro-inflammatory cytokines (73). The current findings indicated that the maternal FSE could influence the composition of the intestinal microbiota in sows while its mechanism still needed to be further investigated.…”
Section: Discussionmentioning
confidence: 85%
“…A traditional herbal medicine called “Tongxie Yaofang” containing paeoniae lactiflora has been widely used to treat diarrhea-predominant irritable bowel syndrome ( 50 ). A herbal medicine compound containing licorice extract reduced diarrhea rates and improved the nutrient apparent digestibility of piglets ( 51 ). These observations were consistent with our results in the present study.…”
Section: Discussionmentioning
confidence: 99%